ADP-ribosyltransferase-based biocatalysis of nonhydrolyzable NAD+ analogs - Sakari, Moona; Bhadane, Rajendra; Kumar, Sujit; Azevedo, Rita; Malakoutikhah, Morteza; Masoumi, Ahmadreza; Littler, Dene R.; Härmä, Harri; Kopra, Kari; Pulliainen, Arto T. (The Journal of biological chemistry, 2025)
Enzyme promiscuity is the ability of an enzyme to catalyze an unexpected side reaction in addition to its main reaction. Here, we describe a biocatalytic process to produce nonhydrolyzable NAD+ analogs based on the ADP-ribosyltransferase activity of pertussis toxin PtxS1 subunit. First, in identical manner to normal catalysis, PtxS1 activates NAD+ to form the reactive oxocarbenium cation. Subsequently, the electrophilic ribose 1′ carbon of the oxocarbenium cation is subject of an attack by the nitrogen atom of an amino group coupled to nicotinamide mimicking compounds. The nitrogen atom acts as the nucleophile instead of the natural sulfur atom substrate of the human Gαi protein. The invention builds on structural data indicating the presence of an NAD+ analog, benzamide amino adenine dinucleotide, at the NAD+ binding site of PtxS1. This was witnessed upon cocrystallization of PtxS1 with NAD+ and 3-aminobenzamide (3-AB). A pharmacophore-based screening on 3-AB followed by quantum mechanical simulations identified analogs of 3-AB with capacity to react with the oxocarbenium cation. Based on HPLC and mass spectrometry, we confirmed the formation of benzamide amino adenine dinucleotide by PtxS1, and also identified two new chemical entities. We name the new entities as isoindolone amine adenine dinucleotide, and isoquinolinone amine adenine dinucleotide, the latter being a highly fluorescent compound. The new NAD+ analogs emerge as valuable tools to study the structural biology and enzymology of NAD+ binding and consuming enzymes, such as human poly(ADP-ribose) polymerases and bacterial ADP-ribosyltransferase exotoxins, and to advance the ongoing drug development efforts.